Groundwater impacts on stream biodiversity and communities: a review - Emma Land; Chelsea N. Peters (Journal of Freshwater Ecology, 2023)
AbstractGroundwater discharge into streams influences the biodiversity and health of groundwater-dependent stream ecosystems. These localized upwelling zones may act as biodiversity hotspots, or areas with a heightened amount of endemic species richness and abundance when compared to the surrounding locality. This input water creates environments with unique chemical compositions and water temperatures that serve as ideal habitat for various species within the ecosystem. Although difficult to identify and sample, these underwater groundwater–surface water interaction zones are important for fish spawning, benthic macroinvertebrate biodiversity, microbial communities, and aquatic and riparian vegetation. In this review, we highlight the groundwater characteristics that influence stream biodiversity and community structure. We argue for the importance of increased research on biodiversity indicators of groundwater upwelling zones as well as more public involvement through citizen science practices on the indirect and direct relationships between groundwater and dependent stream ecosystems.